Design of Epitope-Based Vaccine Against SARS-CoV-2: An Immuno-Informatics Study: Epitope-Based Vaccine Against SARS-CoV-2 - Kusuma, Kavana Hafil; Widyananda, Muhammad Hermawan; Nafisah, Wirdatun; Grahadi, Rahmat; Christina, Yuyun Ika; Dwijayanti, Dinia Rizqi; Mustikaningtyas, Dewi; Widodo, Nashi; Djati, Muhammad Sasmito (Journal of Tropical Life Science, 2024)
This study aimed to develop an epitope-based vaccine of SARS-CoV-2 S protein through an immuno-informatics study. The whole genome of SARS-CoV-2 sequences was obtained from the GISAID database and then trimmed to obtain the S protein sequences. The alignment was done by Clustal-W of MEGA software. Epitope prediction and modeling were performed by Discotope BepiPred and the PepFold3 web server. The allergic responses and physicochemical characteristics of predicted epitopes were analyzed using the AlgPred and ProtParam from ExPASy. Molecular docking and dynamic stimulation were performed using AutoDock Vina and YASARA. Biovia Discovery Studio 2019 was used to visualize the molecular docking results. The study predicted 3 potential epitopes, including ‘GDEVRQIAPGQTGKIADYNYKLP’ (epitope 1), ‘YTMSLGAENSVAYSNN’ (epitope 2), and ‘VNNSYECDIPI’ (epitope 3) located in the spike head specifically RBD region. The epitopes did not show an allergen reaction based on IgE epitope mapping. The suitable overexpression for the host of epitopes was mammalian cells. Only epitopes 1 and 2 were stable (instability index above 40). Epitopes 1, 2, and 3 interacted with BCR with binding affinity values -6.6, -7.8, and -7.5 kcal/mol. Epitope 2 wasere stable when interacting with the BCR. Therefore, three epitopes were predicted to have high potency as the SARS-CoV-2 epitope-based vaccine.